COVID‐19 pandemic: Burdens on and consequences for nursing home staff. (14th March 2022) - Hoedl, Manuela; Thonhofer, Nina; Schoberer, Daniela
Abstract: The objective of this study was to assess burdens placed on and consequences of the COVID‐19 pandemic on nursing home staff. Design: We conducted a qualitative descriptive interview study. Methods: We interviewed 18 nurses, nursing aides and care aides from five different nursing homes by using a semi‐structured interview guideline between June and September 2020. Data were analysed with a qualitative content analysis method by combining an inductive and deductive coding frame. Results: Results show that the qualitative work load and work organization were major concerns. Regarding the qualitative work load, participants stated that they were required to perform additional tasks to care for residents, because the pandemic interventions placed the residents under stress and dealing with relatives presented significant challenges. Nursing home staff reported that psychological consequences such as uncertainty, fear and stress represented major effects of the COVID‐19 situation. Conclusion: We could show that qualitative workloads were assessed and perceived differently. Most nursing home care staff members experienced the changes in working conditions as both physically and psychologically challenging. Impact: We highly recommend that nursing home staff receive support in such pandemics by being allowed, for example personal protective equipment breaks. Individually tailored programs need to be established to enhance wellbeing and decrease psychological stress and fear in such challenging times.